2016
DOI: 10.17507/jltr.0703.14
|View full text |Cite
|
Sign up to set email alerts
|

Iranian English Teaching Applicants' Request and Apology Speech Acts: Special Focus on Language Proficiency

Abstract: Abstract-Considering speech act formulas as one tenet of pragmatics has been one primary aspect of research domain in the recent years. The current study probes whether proficiency level plays any part in implementing request and apology speech acts, with special focus on Iranian English Teaching Applicants (ETA). To calculate participants' pragmatics performance, two Discourse Completion Tests (DCT) were administered, i.e. a multiple choice (MDCT) and a written form (WDCT), each of which was comprised of 10 r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…On a similar account, Istifci (2009) and Qorina (2012) added that higher proficiency learners were inclined to use a wider range of apology strategies and make more complex apology patterns. However, these findings are opposed by Khorshidi, Mobini and Nasiri (2016) and Mohebali and Salehi (2016) who argued that there were no significant differences in the use of apology strategies between learners of high and those of low proficiency levels. Tabatabei and Farnia (2015), in a wider scope, further claimed that there was no positive correlation between proficiency level and pragmatic competence.…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…On a similar account, Istifci (2009) and Qorina (2012) added that higher proficiency learners were inclined to use a wider range of apology strategies and make more complex apology patterns. However, these findings are opposed by Khorshidi, Mobini and Nasiri (2016) and Mohebali and Salehi (2016) who argued that there were no significant differences in the use of apology strategies between learners of high and those of low proficiency levels. Tabatabei and Farnia (2015), in a wider scope, further claimed that there was no positive correlation between proficiency level and pragmatic competence.…”
Section: Introductionmentioning
confidence: 74%
“…These studies suggest the existence of noticeable effects of proficiency level on the use of apology strategies. On the other hand, a counter argument was offered by other researchers such as Khorshidi, Mobini and Nasiri (2016) who reported the absence of significant differences in request and apology speech act production among English teaching applicants of two different proficiency levels. Similarly, Mohebali and Salehi (2016), studying the production of request and apology among Iranian EFL university students, found a negative correlation between language proficiency and knowledge of cross-cultural speech act.…”
Section: Research Questionmentioning
confidence: 95%
“…The knowledge and pragmatic awareness is essential for smooth social interaction in the target language. Many a studies have mentioned that non-native speakers (NNS) often embarrass themselves by their miscommunication and fail to restore interpersonal relations owing to lack of appropriate pragmatic knowledge (Khorshidi Mobini & Nasiri, 2016). In this regard, the present research focuses on the investigation of pragmatic transfer in English-using Pakistanis apology responses (ARs) to highlight any difference if exist among Pakistani English users, British English speakers and Pakistani Urdu speakers.…”
Section: Apology Acceptance Strategiesmentioning
confidence: 98%
“…Furthermore, these studies have shown that L2 learners with higher proficiency are inclined to use a wider range of apology strategies (Li & Suleiman, 2017;Qorina, 2012). However, some other studies have revealed that language proficiency has no effect on the pragmatic competence of apology strategies (Arghamiri & Sadighi, 2013;Farashaiyan & Hua, 2012;Khorshidi et al, 2016). Recently, Cedar (2017) focused on the effects of English proficiency on the apology strategies used by Indonesian EFL learners from two English proficiency levels.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, previous studies on the influence of language proficiency on pragmatic competence have reported controversial findings. While some studies have revealed that language proficiency positively affects pragmatic competence (e.g., Al-Gahtani & Roever, 2012;İstifçi, 2009;Qorina, 2012;Rastegar & Yasami, 2014), other studies have reported that language proficiency has no effect on pragmatic competence (e.g., Farnia & Suleiman, 2009;Khorshidi, Mobini, & Nasiri, 2016;Rastegar & Yasami, 2014). However, the effect of English language proficiency on the production and comprehension of strategies of apology among students of English as a foreign language (EFL), especially young students in schools, has not been widely considered in ILP studies.…”
Section: Introductionmentioning
confidence: 99%